Rutting Performance Evaluation Using Waste Cooking Oil and Ground Tire Rubber in Asphalt Mixture - Ekarizan Shaffie,; Norfarah Nadia Ismail,; Nur Athirah Lokman,; Juraidah Ahmad,; Wardati Hashim,; M. A. Shafii,; Nur’aina Syamimi Nazri, (International Journal of Integrated Engineering, 2025)
The quality of road pavement is a critical factor in establishing an efficient transportation system. To address issues like fatigue cracking and rutting, significant efforts have been devoted to enhancing pavement quality and adopting innovative design approaches. Recent years have seen a growing interest among traffic engineers in improving asphalt performance by incorporating various additives and substituting traditional asphalt binder materials with recyclable alternatives. This study involves blending bitumen grade 80/100 with varying percentages (0%, 1%, 2%, 3%, and 4%) of waste cooking oil (WCO) and 20% ground tyre rubber (GTR), relative to the weight of the bitumen. The physical and rheological properties of both the base bitumen and the modified binder were assessed through penetration, softening point, and dynamic shear rheometer (DSR) tests. As a result of this modification, the specifications of the modified binder are expected to align with those of bitumen grade 40/50, rendering bitumen 80/100 obsolete due to its subpar performance. The research findings indicate that the optimal content for the modified binder is 1% WCO and 20% GTR. Furthermore, the Resilient Modulus (RM) test demonstrates that asphalt mixtures featuring GTR/WCO-modified binders exhibit a reduced susceptibility to rutting compared to conventional bitumen-based asphalt mixtures. This suggests the potential for more durable and rut-resistant road surfaces, aligning with the broader goal of improving transportation infrastructure.